Sex-based differences in trunk acceleration and landing posture during the drop vertical jump test - Sasaki, S.; Shimada, Y.; Nagano, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate sex-based differences in trunk acceleration and landing posture during the drop vertical jump test and to determine the relationships among relevant variables. Twenty college students (10 men and 10 women) performed drop vertical jumps from a 30cm high box. Trunk acceleration and the trunk, limb, knee, and ankle angles in the sagittal plane were measured. The unpaired Student t-test and Pearson product-moment correlation coefficients were used for statistical analysis. Female participants demonstrated greater vertical trunk acceleration and smaller trunk angles than male participants did. In addition, vertical acceleration correlated with trunk and limb angles. Therefore, these parameters, which can be estimated by using wearable sensors, may be useful for checking athletes at high risk for injury.